COMPARATIVE EVALUATION OF IN VITRO ANTIOXIDANT POTENT OF THE MARINE ACTINOBACTERIA FROM GULF OF MANNAR BIOSPHERE RESERVE - KANNAN KAMALA; VALLIAPPAN KARUPPIAH; KANNAN SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2013)
The present study was carried out to evaluate the in vitro antioxidant activity of actinobacteria isolated from the sediments of coral reef environment of the Gulf of Mannar Biosphere Reserve, India. Among 86 strains, five actinobacterial strains (PM15, PM16, PM17, PM18 and PM19) were tested for antioxidant potential, using standard methods. The most active strain PM17 was identified using chemotaxonomical and molecular taxonomical methods. Out of 6 different isolates, PM17 (Streptomyces sp.) showed higher antioxidant activity with an ascorbic acid equivalent of 204.16 ±0.408. Total reducing power was 81.66±0.577 μg/ml and scavenging of hydrogen peroxide and nitric oxide 66.29% and 60.30% respectively. Quantitative analysis of the scavenging assays of the strains assured the presence of antioxidant activity of the respective strains. The most active strain PM17 was taxonomically identified as a species of Streptomyces.